Investigation of the mathematical model of the automatic control system - Rimas, Jonas (Lietuvos matematikos rinkinys, 1999)
The mathematical model of the mutual synchronization system composed of 7 joined into a ring oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.